The Relationship Between Self-Motivation in Compliance in Taking OAT and ARV Medication Towards Side Effects in Tb-HIV Patients - Elfira, Yenni; Irwadi, Irwadi; Fatimah, Fatimah (Indonesian Journal of Global Health Research, 2023)
TB-HIV patients are expected to routinely undergo OAT and ARV treatment simultaneously, this causes the side effects of drugs in patients to be double, resulting in many patients who are not compliant in undergoing treatment. Non-compliance will result in treatment resistance. The purpose of this study was to determine the relationship between self-motivation in adherence to taking OAT and ARV drugs and side effects in TB-HIV patients at Dr. M. Djamil Padang General Hospital. The study design was observational with a cross-sectional approach. The number of samples was 60 people, the sampling technique used Total Sampling. With the respondent criteria that have been determined according to the inclusion and exclusion criteria. The test results showed that patient motivation has a p value of 0.000, drug side effects (0.000), It can be concluded that services for TB-HIV patients must provide education to patients and their families about the need to have medication adherence. With this education, patients will have good adherence so that the success rate of treatment is higher.